2009
DOI: 10.1016/j.aquaculture.2009.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression after total replacement of dietary fish meal and fish oil by plant products in rainbow trout (Oncorhynchus mykiss) liver

Abstract: Our objective was to analyse the hepatic transcriptomes of juvenile rainbow trout fed with a plantbased diet. We focused our analysis on the total replacement of fish meal (FM) and fish oil (FO) by a 100% plant-based diet (0% FM, 0% FO). We analysed the postprandial hepatic transcriptomes of rainbow trout fed the two diets 8 h after feeding. Six total hepatic RNAs from each dietary group were hybridised against a trout cDNA microarray (9K). After treatment of the data respecting the standard MIAME (Minimum Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
103
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 50 publications
19
103
1
2
Order By: Relevance
“…The observed hepatosomatic index of 0.98 to 1.07 in rainbow trout fed diets containing up to 30% PSG is similar to that reported by Barrows et al [53] and Panserat et al [65] for rainbow trout fed fish meal or other plant-based diets. However, these values are much lower than those from other studies which fed soybean meal or other soybean products [48,50,52,53].…”
Section: Discussionsupporting
confidence: 75%
“…The observed hepatosomatic index of 0.98 to 1.07 in rainbow trout fed diets containing up to 30% PSG is similar to that reported by Barrows et al [53] and Panserat et al [65] for rainbow trout fed fish meal or other plant-based diets. However, these values are much lower than those from other studies which fed soybean meal or other soybean products [48,50,52,53].…”
Section: Discussionsupporting
confidence: 75%
“…Recent results showed that the HSI increase was accompanied by elevated liver lipid content in fish fed higher plant protein diets (Sitjà-Bobadilla et al 2005;de Francesco et al 2007;Kjaer et al 2009). Panserat et al (2009) observed an over-expression of genes involved in liver lipid biosynthesis (CHO metabolism and desaturation of polyunsaturated fatty acids) in rainbow trout fed the 100% plant diet (versus the FM-based diet). In addition, liver lipid was also positively correlated with serum TG and negatively correlated with HDL-C (Kotronen and Yki-Järvinen 2008).…”
Section: Discussionmentioning
confidence: 93%
“…Nutrigenomics, by providing global gene expression patterns under different dietary conditions, can provide an improved understanding of how overall nutrition or the inclusion of specific dietary ingredients influences metabolic pathways and, potentially, animal performance. This approach has been successfully used to investigate changes in gene expression in Atlantic salmon liver resulting from partial replacement of fish oil with vegetable oil (Jordal et al, 2005;Leaver et al, 2008) and growth hormone transgenesis (Rise et al, 2006), in rainbow trout liver after varying dietary fish oil levels (Panserat et al, 2008) or total replacement of fish protein and oil with vegetable products (Panserat et al, 2009), and in intestine of rainbow trout deficient in phosphorus (Kirchner et al, 2007). We now have identified genes that are differentially regulated in Atlantic halibut in response to replacement of FM with SBM.…”
Section: Discussionmentioning
confidence: 99%